Non-coding RNA in rhabdomyosarcoma progression and metastasis - Ramadan, Farah; Saab, Raya; Hussein, Nader; Clézardin, Philippe; Cohen, Pascale A.; Ghayad, Sandra E. (Frontiers in Oncology, 2022)
Rhabdomyosarcoma (RMS) is a soft tissue sarcoma of skeletal muscle differentiation, with a predominant occurrence in children and adolescents. One of the major challenges facing treatment success is the presence of metastatic disease at the time of diagnosis, commonly associated with the more aggressive fusion-positive subtype. Non-coding RNA (ncRNA) can regulate gene transcription and translation, and their dysregulation has been associated with cancer development and progression. MicroRNA (miRNA) are short non-coding nucleic acid sequences involved in the regulation of gene expression that act by targeting messenger RNA (mRNA), and their aberrant expression has been associated with both RMS initiation and progression. Other ncRNA including long non-coding RNA (lncRNA), circular RNA (circRNA) and ribosomal RNA (rRNA) have also been associated with RMS revealing important mechanistic roles in RMS biology, but these studies are still limited and require further investigation. In this review, we discuss the established roles of ncRNA in RMS differentiation, growth and progression, highlighting their potential use in RMS prognosis, as therapeutic agents or as targets of treatment.